THE ROLE OF HOLONIC INDUSTRIAL IN ENHANCING PRODUCT QUALITY: AN INVESTIGATIVE STUDY IN NORTH OIL COMPANY - Abdullah Muhammad Suleiman (Journals Park Publishing, 2025)
The current study aims to determine the role of Holonic Manufacturing in enhancing product quality across its three dimensions (performance, reliability, durability). To achieve the research objective and answer the questions raised by its problem, the most prominent of which was: "What is the nature of the correlation and impact relationships between Holonic Manufacturing and product quality?" a random sample of 40 employees from North Oil Company was selected. A questionnaire was used as the primary tool for data collection from the surveyed company. For data analysis, the researcher relied on the (SPSS V25) program. The research concluded with several findings, the most significant of which was the existence of a meaningful correlation and impact relationship between Holonic Manufacturing and product quality. Based on this, a set of recommendations was presented to the management of the surveyed company, the most notable of which was the necessity of increasing attention to all means that could enhance product quality within the company.
Keywords: Holonic Manufacturing, Product Quality, Reliability.